2023
DOI: 10.3390/ijms242115973
|View full text |Cite
|
Sign up to set email alerts
|

Reference Genes Screening and Gene Expression Patterns Analysis Involved in Gelsenicine Biosynthesis under Different Hormone Treatments in Gelsemium elegans

Yao Zhang,
Detian Mu,
Liya Wang
et al.

Abstract: Reverse transcription quantitative polymerase chain reaction (RT-qPCR) is an accurate method for quantifying gene expression levels. Choosing appropriate reference genes to normalize the data is essential for reducing errors. Gelsemium elegans is a highly poisonous but important medicinal plant used for analgesic and anti-swelling purposes. Gelsenicine is one of the vital active ingredients, and its biosynthesis pathway remains to be determined. In this study, G. elegans leaf tissue with and without the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Moreover, previous studies have indicated that plants subjected to abiotic stress exhibit increased yields of secondary metabolites, accompanied by changes in the expression levels of relevant biosynthetic genes [23][24][25]. It has been demonstrated that the application of methyl jasmonate (MeJA) leads to an augmentation in the synthesis and accumulation of tanshinones and phenolic acids within the hairy roots of Salvia miltiorrhiza.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have indicated that plants subjected to abiotic stress exhibit increased yields of secondary metabolites, accompanied by changes in the expression levels of relevant biosynthetic genes [23][24][25]. It has been demonstrated that the application of methyl jasmonate (MeJA) leads to an augmentation in the synthesis and accumulation of tanshinones and phenolic acids within the hairy roots of Salvia miltiorrhiza.…”
Section: Introductionmentioning
confidence: 99%
“…In Euodia rutaecarpa, the expression patterns of HMGCR, SQE, and CYP450 calculated by screened reference genes were consistent with the content of limonin, thus implying their potential involvement in the limonin biosynthesis of E. rutaecarpa. Furthermore, qRT-PCR was used to analyze the expression patterns of 15 genes involved in the terpenoid indole alkaloids pathway using stable reference genes, and three key enzyme genes were found to have strong correlations with the gelsenicine in Gelsemium elegans [13,14]. qRT-PCR has high sensitivity, high specificity, and simple operation [15].…”
Section: Introductionmentioning
confidence: 99%